2021
DOI: 10.31219/osf.io/dhwqv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cervical Cancer Screening Cascade for women living with HIV: a cohort study from Zimbabwe

Abstract: Background. We defined a cascade of cervical screening to evaluate the number of women living with HIV (WLHIV) achieving each cascade stage at an HIV care and treatment clinic in Zimbabwe. Methods. We included women aged ≥18 years enrolled at the Newlands Clinic in Harare from June 2012 to June 2017 and followed them until June 2018. The cascade consists of screening and preventative treatment arms based on initial screening results. We report percentages, the median time to reach cascade stages, and cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The sample size of females aged 25-49 years ranged from 5882 in Ethiopia to 9186 in Tanzania. The median age and interquartile ranges were 32 years (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in Ethiopia, 33 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Zambia and 34 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Malawi, Rwanda, and Tanzania. The rate of self-reported cervical pre-cancer screening was lowest in Rwanda (3.5% [95% CI 3.1%-4.0%]) and highest in Zambia (17.1% [95% CI 15.8%-18.5%]) and Zimbabwe (17.4% [95% CI 16.1%-18.8%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of females aged 25-49 years ranged from 5882 in Ethiopia to 9186 in Tanzania. The median age and interquartile ranges were 32 years (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in Ethiopia, 33 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Zambia and 34 years (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Malawi, Rwanda, and Tanzania. The rate of self-reported cervical pre-cancer screening was lowest in Rwanda (3.5% [95% CI 3.1%-4.0%]) and highest in Zambia (17.1% [95% CI 15.8%-18.5%]) and Zimbabwe (17.4% [95% CI 16.1%-18.8%]).…”
Section: Resultsmentioning
confidence: 99%
“…One reason may be the perception that linking women testing HIV positive to HIV treatment eliminates the risk of cervical pre-cancer for such women. A study in Zimbabwe found that many women living with HIV on ART screened positive for cervical pre-cancer, despite the country attaining HIV treatment targets [33].…”
Section: Discussionmentioning
confidence: 99%